I FAITH IN C.S LEWIS ‘’THE LION, THE WITCH, AND THE WARDROBE’’ - Rika Hidayatun Nikmah; Elisabeth Z. Oroh; Jennie Posumah (Program Studi Pendidikan Bahasa Inggris, 2022)
People usually has their own faith whether it is related to the religious aspect or others, from time to time the discussion about faith still become the interesting topic because it can bring the positive impact for man live or in the contrary negative effect. In Faith defined as general religious attitude or accepted set of personal beliefs. Faith has been a part of religion, and explored by scholars from numerous disciplines. The present discussion focuses on theistic religious faith as a paradigm of the kind of faith that is of interest, though the question of faith outside this context is taken up in the final Section. The purpose of the research is to find out about faith in the novel written by C.S Lewis entitled the Lion, The witch, and the Wardrobe. This research is categorized as qualitative research because the data collected in the form of words rather than numbers. Objective approach is applied in analyzing the data. Research finding shows that there are some types of faith, they are faith to the existence of Narnia, faith to Aslan existence, and faith to God.